Vivienda multifamiliar como elemento de densificación y renovación urbana en la zona céntrica del municipio de Yumbo. (2023)
The research presented below proposes the center of the municipality of Yumbo as the study area, as the area with the highest urban complexity at present, due to the presence of multiple social, cultural, economic dynamics and diverse lifestyles, that over time are transformed and are affected by the inclusion of new actors that introduce problems and needs to be satisfied. This situation offers gigantic opportunities for analysis and research fields in the interest of maintaining the vitality of the center.